Characteristics of roe deer bot fly infection in the southern part of the Great Hungarian Plain - Pinnyey, Szilárd (Acta Agraria Debreceniensis, 2012)
I am investigating the occurance of one of the diseases caused by parasites in plain roe deer populations, namely a botfly larvae, Cephenemyiastimulator, (Clark, 1815) ranged among the Oestridae family. Nasal botfly larvae are common roe deer parasites and are generally spread nationwide. The subject of the present survey is the processing of the data gained about roe deer bucks of the year 2009 and their infestation indices. I investigated botfly larvae in 90 bucks’ nasal and pharyngeal cavity. We have found botfly larva in 18.9% of the examined bucks (prevalence), this means 17 infected specimen. I collected 218 pieces of larvae from the samples, with a 12.8 pieces average intensity. In my investigations prevalence was lower and mean intensity was higher than in previous Hungarian researches. This was manifested both in my overall data, and in our examinations by the different age groups.